KEY FACTORS INFLUENCING WOMEN’S PARTICIPATION IN FAMILY PLANNING PROGRAMMES - Sirazudeen, Nurhaslinda; Darwin, Eryati; Yetti, Husna (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: Family planning is a government programme designed to address population needs and balance demographic pressures. It generally aims to regulate the number of births to reduce the risks associated with pregnancy. Contraception serves as a tool for managing pregnancy and controlling childbirth. Women’s participation in family planning programmes is influenced by both internal and external factors. Methods: This research is an analytical study with a cross-sectional design, conducted at Puskesmas Alai, Kota Padang, with a total sample of 105 married women. The study utilized a questionnaire to assess internal and external factors related to women's involvement in the family planning programme. Data were analyzed using the chi-square test. Results: The results of this research indicate that the number of respondents who use contraception is greater than those who do not. Regarding internal factors, most respondents fall into the risk age group, have a high level of education, are not employed, possess a good level of knowledge, and have 0 to 2 children. For external factors, the majority of respondents receive support from their husbands, and more than half of the respondents have a low economic status. Conclusion: The conclusion of this research is that there is a significant correlation between age, knowledge level, husband's support, and economic status with participation in the family planning programme. However, no significant correlation was found between education, occupation, and the number of children.